MENGUNGKAP MAKNA IT BALANCED SCORECARD: STUDI FENOMENOLOGI PADA SATU PERGURUAN TINGGI DI JAKARTA BARAT - Sarwo Edy Handoyo; Herlin Tundjung Setijaningsih; Ary Satria Pamungkas (Jurnal Manajemen., 2013)
Implementing information and communication technology (ICT) penetrated into all aspheres of life including college. Basically college runs three main aspects of process, content, and resources. Given the impementation of ICT to manage the three aspects will require investment and operation costs are relatively large, it is necessary to measure the effectiveness and productivity. The method of measurement used is the IT balanced scorecard. In Jakarta, many universities are using IT to manage its acttivities. However, applying the IT balanced scorecard, not many. One college in West Jakarta has implemented IT balance scorecard well. The purpose of this study was to determine the meaning of the IT balanced scorecard according to one college administrator in West Jakarta. The research method use is qualitative with interpretive paradigm and methodology of phenomenology. The results showed significance for the management of IT balance scorecard college X is a performance measure of IT to facilitate achieving the performance in perspective of human resources, opaerations, user, and corporate contribution. By using the IT BSC, the data is always updated so that decisions can be made quickly and appropriately, can continously improved stakeholders satisfaction, efficiency and effectiveness of management can be achieved.